Eksistensi Laki-Laki Dalam Gerakan Feminisme Islam - Siti Amallia (Jurnal Kawakib, 2022)
Interest in women's issues does not only come from women's groups, but also from men's groups. The word "masculine" which is often attached to men and "feminine" to women is in fact a form of social construction which in practice is absolutely interchangeable. It is important to trace the existence of men in the Islamic feminism movement with the aim of seeing how religion regulates the position of men and tracing the causes of discrimination against women under the guise of religion. This research is included in library research that refers to several scientific sources such as books, journals and the internet. The method used is historical continuity and interpretation to trace history and its relation to actual issues related to the existence of men and the Islamic feminism movement. From the results of the study, it was found that the existence of men in the Islamic feminism movement is a form of concern and support for issues related to gender inequality and violence against women in the name of religion as the basis of Islamic law. In addition to thinking support, the researcher also found that there was support in terms of action. For example, the campaign from the New Men's Alliance which supports the gender equality movement, that there is nothing wrong if men also help in the domestic area because cleaning the house and taking care of children is not an absolute nature of women. In addition, the existence of men can also be seen from the ideas of characters such as Asghar Ali Engineer and KH Husein Muhammad. In general, both are equally critical of the conservative views of Muslims. Criticizing the commentators who only use the Qur'an and Hadith as the only source of Islamic law without contextualizing it with the progress of civilization. As a result, misogynistic verses appear that are detrimental to one party, in this case women.